2017
DOI: 10.1016/j.jgr.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on chemical composition of total saponins extracted from fermented and white ginseng under the effect of macrophage phagocytotic function

Abstract: In this study, white ginseng was used as the raw material, which was fermented with Paecilomyces hepiali through solid culture medium, to produce ginsenosides with modified chemical composition. The characteristic chemical markers of the products thus produced were investigated using rapid resolution liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (RRLC–QTOF–MS). Chemical profiling data were obtained, which were then subjected to multivariate statistical analysis for the systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Ginsenoside 20(S)-Rg3 of trace amount is naturally present in P. ginseng and is generally thought to be the major thermal decomposition product [5], [16], [26]. To clarify the origination of the detected 20(S)-Rg3, a raw ginseng sample was extracted simultaneously by the ultrasonic extraction method and the reflux extraction method as ultrasonic vibration could avoid the decomposition of thermal-sensitive ginsenosides [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginsenoside 20(S)-Rg3 of trace amount is naturally present in P. ginseng and is generally thought to be the major thermal decomposition product [5], [16], [26]. To clarify the origination of the detected 20(S)-Rg3, a raw ginseng sample was extracted simultaneously by the ultrasonic extraction method and the reflux extraction method as ultrasonic vibration could avoid the decomposition of thermal-sensitive ginsenosides [3].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous report indicated that the individual content of five major ginsenosides differed significantly with the ginseng samples, which were collected from three different cultivation regions [14]. In addition, commercial ginseng products such as red ginseng and black ginseng are normally pharmacologically superior to their original forms due to the rich content of rare ginsenosides [12], [13], [15], [16]. However, rare ginsenosides are scarcely naturally occurring in cultivated ginseng and can be obtained only by the transformation of major ones [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The fermented Korean red ginseng not only increases the ginsenoside content inherent in Korean ginseng but also produces special ginsenosides such as Rg 2 and Rg 3 . 28,29 The saponin fraction of ginseng is composed of various ginsenosides. 30 We enriched ginsenosides by fractionating saponins from red ginseng extract and removing sugar and protein.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially different mechanisms might be involved, and other indicators of inflammation, such as the expression of proinflammatory and anti-inflammatory genes, level of protein and lipid mediators of inflammation, and post-translation modification of key enzymes, have yet to be studied. The potential phagocytic function of macrophages of ginseng extracts has been evaluated recently using a different zebrafish model [108].…”
Section: Zebrafish As a Model For Research On The Effect Of Red Ginsementioning
confidence: 99%